2012
DOI: 10.1109/tasc.2011.2176300
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Conventional/Enhanced Permanent Magnet Method: Influence of Crack on Accuracy

Abstract: The conventional and enhanced permanent magnet methods for measuring the critical current density in a high-temperature superconducting (HTS) tape have been simulated numerically. Moreover, the influence of the crack on the accuracy of the conventional method has been investigated. In order to simulate both permanent magnet methods, two types of numerical code have been developed for analysing the time evolution of a shielding current density in an HTS tape. The results of computations for the conventional met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Under the thin-plate approximation, there exists a scalar function T (x, t) such that j = (2/b)∇ × (T e z ), and its time evolution is governed by the following integrodifferential equation [7], [8], [13], [14]:…”
Section: B Formulation By T-methodsmentioning
confidence: 99%
“…Under the thin-plate approximation, there exists a scalar function T (x, t) such that j = (2/b)∇ × (T e z ), and its time evolution is governed by the following integrodifferential equation [7], [8], [13], [14]:…”
Section: B Formulation By T-methodsmentioning
confidence: 99%
“…As a result, they showed that the SPM can be ap- plied to the measurement of the j C -distribution [6]. However, it is not clear whether or not cracks can be identified by using the SPM.…”
Section: Introductionmentioning
confidence: 99%